IMPLEMENTASI RAPID APPLICATION DEVELOPMENT PADA PEMODELAN SISTEM INFORMASI APOTEK - Sala, Elvira Esperanza; Togo, Rosalin (LPPM Institut Teknologi Bisnis Dan Bahasa Dian Cipta Cendikia, 2023)
Analysis and design are the basis for the development of information systems, because it is important to make them in detail and complete, so that the next steps can be carried out effectively and efficiently. The analysis and design of this pharmacy information system is made to identify the needs of pharmacies and users for the system built, as well as to design the user interface and database needed for its implementation. The system was built using the Rapid Application Development (RAD) model. The RAD method allows the involvement of the user in reviewing the design, so that the design results can correctly answer the user's needs. The first RAD stage in this research is business modeling. At this stage, an analysis of all user requirements for the system to be designed is carried out. Data for analysis was obtained through direct interviews with users, as well as through direct observation at the research site. Users of the system that was built consisted of pharmacists and pharmacy employees, each with the authority to access rights in the system. In the next stage, data modeling is carried out based on the results of the needs analysis. Data modeling consists of entity relationship diagrams (ER diagrams) and table relationships. ER Diagram includes 4 entities, namely users, purchases, goods, and sales. Each entity has its own attributes. Referring to the ER diagram, a table relation is created to visualize the tables and fields in the database. The third stage is process modeling, which is explained through use case diagrams and activity diagrams. Use case diagrams explain what processes can be carried out by each actor, while activity diagrams describe all activities that occur in the system. The last design process is user interface design. The user interface provides an overview to the user about the appearance of the system that will be seen by the user. System design through several changes at the request of the user. The results of the research are in the form of designs for the implementation phase. The resulting design will facilitate the programmer's task because the design has been approved by the user so that it can be a strong basis in building an information system that has minimal errors. The system implementation phase will be more targeted and efficient in terms of time.